SOCIETAL PERCEPTION OF ILLNESS AND RELATIONSHIP WITH ILL PERSONS - Gedzi, Victor Selorme (European Scientific Journal, ESJ, 2013)
The paper analyses societal perception of some major illnesses such as leprosy, cancer, tuberculosis and HIV/AIDS and the influence of the perception on people’s relationship with victims of such illnesses. The study is important because it may contribute to correction of the perception thereby making people relate well with ill persons. The research finding shows that people’s perception of an illness is influenced by benign beliefs and speculations. The perception stigmatizes certain illnesses as evil. The finding further shows that people’s perception of the illnesses and resultant relationships with the ill is wrong and must be changed.